Application of Problem Based Learning Models to Improve Critical Thingking Skills Mathematically in science two tenth grade class students of Senior High School 1 Salo - Fany Novita Sari (Mathematics Research and Education Journal, 2018)
Abstract This study aims to improve the learning process and improve mathematical critical thinking skills of students of class X IPA-2 SMA Negeri 1 Salo on trigonometric material through the application of Problem Based Learning (PBL) models. This research is a Class Action Research (CAR) which consists of two cycles. The subjects of this study were students of class X IPA-2 SMA Negeri 1 Salo in the academic year 2017/2018 as many as 32 students consisting of 21 female students and 11 male students. Data collection instruments in this study were observation sheets, guidelines for scoring mathematical critical thinking skills, tests and documentation. Data collection techniques in this study are observation techniques and test techniques. The data analysis technique in this study is the analysis of data from the observation and analysis of test results data. The results of this study indicate that there is an improvement in the learning process and an increase in mathematical critical thinking skills of students of class X IPA-2 SMA Negeri 1 Salo. This can be seen from the percentage of students' critical thinking skills before the action and after the action, namely cycle I and cycle II. Before the action, the average percentage of students' critical thinking skills at 60.93% is on the less critical criteria. After being given an action, it increased to 73.82% with a critically sufficient criterion at the end of cycle I and increased to 85.35% at the end of cycle II which reached critical criteria. So it can be concluded that the application of the Problem Based Learning (PBL) model can improve the learning process and improve the ability to think critically mathematically in the tenth grade students of SMA Negeri 1 Salo in the academic year 2017/2018.